Generalized Hybrid Viscosity-Type Forward-Backward Splitting Method with Application to Convex Minimization and Image Restoration Problems. (3rd October 2021) - Chidume, C. E.; Adamu, A.; Kumam, P.; Kitkuan, D.
Abstract: Let E be a uniformly convex and q-uniformly smooth real Banach space. Let A : E → E be an α- inverse strongly accretive mapping of order q, B : E ⊸ E be a set-valued m- accretive mapping and S : E → E be a nonexpansive mapping . In this article, a viscosity-type forward-backward splitting method for approximating a zero of ( A + B ) which is also a fixed point of S is introduced studied. Strong convergence theorem of the method is proved under suitable conditions. Furthermore, the convergence result obtained is applied to convex minimization and image restoration problems. Finally, numerical illustrations are presented to compare the convergence of the sequence of our algorithm and that of some recent important algorithms.